Substance misuse and parenting: making drugs and gender in the family court. Issue 4 (December 2019) - Flacks, Simon
Abstract: Children tend to be represented as the quintessential victims of the 'drug problem', with drug-using parents, particularly mothers, characterised as vectors of the risks posed. Although evidence of drug use is not per se an impediment to retaining care of, or contact with, children (per Lady Hale in Re B [2013] UKSC 33, at para. 143), it does pose one of the greatest challenges to social and political norms about 'good parenting', and often has a powerful impact on decisions about care within UK family courts. While there is a considerable body of scholarship assessing criminal justice responses to drug use, there has been little research into how the family serves as an important site for the constitution of drug harms and the making of 'drugs' and 'addiction'. This paper is informed by qualitative analysis of approximately 150 case reports in which drug use has been cited as relevant in the determination of guardianship/parenting. The purpose will not be to contest the difficult decisions that judges had to make in these cases but, using perspectives rooted in Science and Technology Studies and feminist drug scholarship, to remain attendant to the ontological multiplicity of objects that emerge from attempts to stabilise drug harms in legal narratives.